Nanoparticle based amperometric biosensor for the quantitative determination of cholesterol in human blood - RAID SALEEM AL BARADIE,; ANANDH SAM CHANDRA BOSE, (International Journal of Pharma and Bio Sciences, 2017)
Total cholesterol monitoring in human blood serum is one of the most important routine analysis performed in clinical laboratory. There is a strong correlation between coronary heart disease and blood cholesterol level. Numbers of cholesterol biosensors have been developed over the past 30 years. Cholesterol is determined enzymatically by Fibre-optic fluorescence, Fibre-optic luminescence, Potentiometric, Spectrophotometric and Fluorometric biosensors. Some of these methods suffer from interference from other substances found in the blood such as ascorbic acid and uric acid. There is need for a method that is sufficiently flexible to yield good results in clinical laboratory. The attributes of the enzyme linked platinum electrode was studied with cholesterol powder solution using cyclic voltammeter 797 VA. The peak value of the current from the electrode was detected with the input potential changes from +0.5 V to -1 V. The Mann Whitney U Test was conducted for the sampled data, the results show that the data is significant with α = 0.05. Fabricated amperometric biosensor was found to be sensitive in determining the cholesterol level in the human blood.